The education of medical librarians in Nigeria search for an appropriate programme - Afolayan, Olusegun Samuel O.; Dimalanta, Clarisa G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1983)
The education of medical librarians was explored from its beginning. It was found that while the special education exists and is desirable, there is no generally accepted standard in the following aspects of their education, namely: the qualifications of the candidates, the type and level of the programme, the subjects in the curriculum, the part to be played by library schools, and the role of the professional association of medical librarians. In view of these, this study was undertaken in order to discover a model that can be recommended to Nigerian library schools.
Two methods were employed in gathering data. The first involved interviewing the librarians in-charge of selected libraries in Metro Manila and the second involved comparing the curricula of selected library schools in the United States of America, Great Britain and the Philippines.
The study revealed that those with a degree in a biomedical science are the best candidates for medical librarianship. The study also showed that the ideal preparation is the degree program at the master's level and that the curriculum should embrace foundation and technical subjects, medical librarianship subjects and applied library science subjects. Medical librarians are advised to allow students to take practicum in their libraries and also to employ biomedical science graduates who could be medical librarians after a medical librarianship course of one year or two. The professional association of medical librarians is urged to be active in organizing and conducting seminars, workshops and other continuing education courses for medical librarians.
Mimeographed.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Library education--Nigeria.; Medical librarians--Nigeria.